Analysis of Effect of Training and Development Determinants on the Job Satisfaction of Employees in Manufacturing Sector - Pandita, Dr.Sarjue (The journal of contemporary issues in business and government, 2023)
Employee performance can be improved by training, which connects job needs to the present job description of the personnel. Aside from that, training is a significant financial and time commitment. The time has come for organizations to examine training programs to see how they affect trainees’ performance and behaviour. When it comes to managing their employees, job satisfaction is one of the most difficult areas to address. Every company’s most valuable resource is its workforce. A company’s success depends on the ability of its employees to perform their jobs effectively and efficiently. Organizations’ on-going efforts contribute to the development of employees’ abilities and capacities.Employees will feel more invested in their jobs when they see evidence that the training program is improving their skills and knowledge. Managers should devise plans to implement or lead training programs that effectively improve workers’ abilities at all levels of the organization. Managers must therefore determine what constitutes a good, attractive, and well-managed training infrastructure. This Paper will focus on studying various determinants of Training and their impact on overall employee satisfaction. Data thus collected has been analysed by using SPSS and AMOS version 26